2018
DOI: 10.1186/s40360-018-0204-7
|View full text |Cite
|
Sign up to set email alerts
|

Sulforaphane attenuates pulmonary fibrosis by inhibiting the epithelial-mesenchymal transition

Abstract: BackgroundIdiopathic pulmonary fibrosis (IPF) is a progressive and fatal disease with no effective treatment. The epithelial-mesenchymal transition (EMT) is a critical stage during the development of fibrosis. To assess the effect of sulforaphane (SFN) on the EMT and fibrosis using an in vitro transforming growth factor (TGF)-β1-induced model and an in vivo bleomycin (BLM)-induced model.MethodsIn vitro studies, cell viability, and cytotoxicity were measured using a Cell Counting Kit-8. The functional TGF-β1-in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
54
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(55 citation statements)
references
References 30 publications
(61 reference statements)
1
54
0
Order By: Relevance
“…This is in agreement with Tanjore et al [14], in which the team reported that about one-third of fibroblasts in lung tissues of BLM-induced pulmonary fibrotic mice was derived from type II lung epithelial cells through the process of EMT. EMT is characterized by low expression of epithelial cell markers such as E-cadherin and ZO-1 and overexpression of mesenchymal markers such as α -Smooth muscle actin ( α -SMA) and vimentin [15, 16]. Meanwhile, TGF- β 1 is regarded as an important triggering factor for the onset of pulmonary fibrosis by accelerating the process of transformation of alveolar epithelial cells into mesenchymal myofibroblasts [17, 18].…”
Section: Introductionmentioning
confidence: 99%
“…This is in agreement with Tanjore et al [14], in which the team reported that about one-third of fibroblasts in lung tissues of BLM-induced pulmonary fibrotic mice was derived from type II lung epithelial cells through the process of EMT. EMT is characterized by low expression of epithelial cell markers such as E-cadherin and ZO-1 and overexpression of mesenchymal markers such as α -Smooth muscle actin ( α -SMA) and vimentin [15, 16]. Meanwhile, TGF- β 1 is regarded as an important triggering factor for the onset of pulmonary fibrosis by accelerating the process of transformation of alveolar epithelial cells into mesenchymal myofibroblasts [17, 18].…”
Section: Introductionmentioning
confidence: 99%
“…Snail is a transcription factor regulating the EMT process, and it could induce EMT through inhibiting the transcription expression of E-Cad. 29,30 N-Cad, a mesenchymal cell marker, does not express in normal epithelial tissues, but its ectopic expression in epithelial tissues can induce EMT, causes tumor cells to develop invasive phenotype and enables distant metastasis. 31,32 The current study showed that knockdown of LINC02471 increased the E-Cad expression level and reduced the N-Cad and Snail expression level in PTC cell lines, suggesting that LINC02471 could enhance the metastasis of PTC by inducing EMT.…”
Section: Discussionmentioning
confidence: 99%
“…Emerging data demonstrate that EMT is the driving force of cancer metastasis [ 38 , 39 ]. During EMT process, the expression of E-cadherin, a epithelial marker, is decreased, while the expressions of mesenchymal markers, Fibronectin, Vimentin, and N-cadherin, are demonstrated to be increased [ 40 ]. According to the present study, the protein levels of Fibronection, Vimentin, and N-cadherin were down-regulated, while E-cadherin level was up-regulated in ESCC cells by miR-133b agomir or shEGFR treatment via targeting modulation of EGFR.…”
Section: Discussionmentioning
confidence: 99%